Pancasila Ethics In The Shadow Of Political Pragmatism: A Strategy For Transforming A Party System With Integrity - Doni ardiansyah; Sunarso (SOSIOEDUKASI, 2026)
This study aims to analyze the role of Pancasila ethics in addressing political pragmatism within Indonesia’s party system and to formulate transformation strategies that can foster a party system characterized by integrity. In Indonesia’s political system, political pragmatism often leads to the neglect of Pancasila values, resulting in political practices lacking integrity, such as transactional politics and corruption. This study employs a qualitative approach with literature analysis to explore the relationship between Pancasila values and the pragmatic political practices occurring in Indonesia. The research findings indicate that to address political pragmatism, political parties in Indonesia need to implement transformation strategies that include character education for party leaders, the application of transparency and accountability in party management, the empowerment of internal democracy, and the strengthening of integrity in the electoral process. This study concludes that the consistent application of Pancasila values in the policies and practices of political parties can foster a party system that is more integrity-driven and accountable to the people.